2012
DOI: 10.1096/fj.12-213454
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic ATGL knockdown uncouples glucose intolerance from liver TAG accumulation

Abstract: Adipose triglyceride lipase (ATGL) is the predominant triacylglycerol (TAG) hydrolase in mammals; however, the tissue-specific effects of ATGL outside of adipose tissue have not been well characterized. Hence, we tested the contribution of hepatic ATGL on mediating glucose tolerance and insulin action. Glucose or insulin tolerance tests and insulin signaling were performed in C57BL/6 mice administered control (nongene specific shRNA) or Atgl shRNA adenoviruses. Glucose and lipid metabolism assays were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 48 publications
6
46
0
Order By: Relevance
“…As mentioned before, in 2006 our group found that ATGL-KO led to fatty liver but not to systemic insulin resistance ( 13 ). This fi nding was supported by a very recent study, where HFD feeding to liver-specifi c ATGL-KO mice enhanced liver TG contents and primary hepatocytes derived from these livers exhibited improved glucose tolerance despite unaltered insulin signaling ( 16 ). Importantly, diseases are known to be caused by inactive ATGL protein due to a genetic defect (neutral lipid storage disease with myopathy) ( 23 ), or to be caused by functional ATGL yet inactive by lack of functional coactivator CGI-58 (neutral lipid storage disease with ichtyosis, Chanarin-Dorfman syndrome) ( 24 ).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…As mentioned before, in 2006 our group found that ATGL-KO led to fatty liver but not to systemic insulin resistance ( 13 ). This fi nding was supported by a very recent study, where HFD feeding to liver-specifi c ATGL-KO mice enhanced liver TG contents and primary hepatocytes derived from these livers exhibited improved glucose tolerance despite unaltered insulin signaling ( 16 ). Importantly, diseases are known to be caused by inactive ATGL protein due to a genetic defect (neutral lipid storage disease with myopathy) ( 23 ), or to be caused by functional ATGL yet inactive by lack of functional coactivator CGI-58 (neutral lipid storage disease with ichtyosis, Chanarin-Dorfman syndrome) ( 24 ).…”
Section: Discussionsupporting
confidence: 66%
“…The latter fi nding, however, was not supported by a subsequent study ( 15 ). Also, hepatic ATGL-KO uncoupled glucose intolerance from liver TG accumulation ( 16,17 ).…”
Section: Determination Of Ld Lipid Profi Les and Molecular Species Bymentioning
confidence: 83%
“…Of interest, both deletion (current study) and overexpression (36) of ATGL in adipocytes improves hepatic steatosis and insulin resistance, suggesting that adipocyte lipolysis may be a therapeutic target for these disorders. In contrast, modulating ATGL action within skeletal muscle (22) and liver (37)(38)(39) do not significantly influence glucose homeostasis and insulin signaling. Interestingly, despite a comparable reduction in adipocyte lipolysis, GAKO mice have increased rather than decreased susceptibility to hepatic inflammation, presumably because hepatic ATGL action is required not only for hepatic lipid homeostasis but for activation of PPAR␣'s anti-inflammatory effects (40).…”
Section: Discussionmentioning
confidence: 85%
“…Mice lacking ATGL show improved glucose tolerance and are resistant to high-fat diet-induced insulin resistance (21)(22)(23). ATGL deficiency also improves insulin signaling in white adipose tissue (21).…”
Section: Catecholamine-induced Inhibition Of Glucose Uptake and Insulinmentioning
confidence: 99%